2021
DOI: 10.3390/ijerph18052596
|View full text |Cite
|
Sign up to set email alerts
|

A Relational Approach to the Design for Peer Support

Abstract: Peer-support services enhance mental wellbeing and increase the knowledge and capabilities of self-help groups in various settings. To ensure that these services foster peer-support relationships as intended, it is necessary to design and assess them from a relational perspective. This study presents a relational framework for peer-support design and its application to two existing peer-support services for solitary seniors in Seoul and Ulsan. The framework aims to support the analysis and conception of peer-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…of Veteran Affairs, 2013; Open Arms: Veterans and Families Counselling, nd). Indeed, the provision of therapeutic support through a peer group model has been shown to be an effective service model delivery (Van Hasselt et al, 2018), particularly in terms of the value placed on its relational features (Pahk and Baek, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…of Veteran Affairs, 2013; Open Arms: Veterans and Families Counselling, nd). Indeed, the provision of therapeutic support through a peer group model has been shown to be an effective service model delivery (Van Hasselt et al, 2018), particularly in terms of the value placed on its relational features (Pahk and Baek, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The provision of adequate resources required to assist transitions from service has been recognised as an important factor for creating new identities, interests and career opportunities (Tufano, 2018; Carney et al, 2021). Increases in social connection and social support as experienced in a peer support program model (Pahk and Baek, 2021) is a material benefit aiding the exploration of future career and interest options.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have shown that people experiencing homelessness support one another, both informally and through formal peer support initiatives ( Dej, 2020 ; Green, Mason, & Ollerenshaw, 2004 ; Guirguis-Younger, McNeil, & Hwang, 2014 ). Peer support initiatives have also been shown to help other groups experiencing marginalization, such as people with mental health issues or who use substances ( Batchelder et al, 2017 ; Boyce, Munn-Giddings, & Secker, 2018 ; Deering et al, 2009 ), people living with HIV ( Roth et al, 2012 ), the isolated elderly ( Pahk & Baek, 2021 ), and individuals with low health literacy, low socioeconomic status, or other disadvantages ( Sokol & Fisher, 2016 ). Yet there is less research on informal peer support networks, including limited investigation of their mutuality.…”
Section: Introductionmentioning
confidence: 99%